Prevalence and determinants of dental caries in a sample of schoolchildren of Sátão, Portugal - Veiga, Nélio (2021)
Objectives: The aim of this study consisted in the assessment of the prevalence of dental caries, dmft and DMFT index among schoolchildren and analysis of the association between oral health behaviors and socio-demographic aspects. Methods: In a cross-sectional study we assessed 605 children aged between 6 and 12 years from 27 public schools of Sátão, Portugal. Dental caries was assessed by performing an intraoral observation. Data concerning children's oral health behaviors and socio-demographic variables were collected through a questionnaire filled out by their parents. Prevalences were expressed in proportions. The continuous variables were described using the mean and standard deviation. The Chi-square test was used to compare proportions and the Kruskal-Wallis test for comparing continuous variables. Results: We verified that the dmft index was 3.01 ± 3.03 and DMFT index was 0.93 ± 1.35. The prevalence of dental caries is associated with age (≤8 years, 37.1% vs 40.0%, p = 0.008), parents' educational level (0-4 years, 4-9 years, >9 years, 41.2% vs 43.7% vs 13.8%, p = 0.001) and residence area (rural, 42, 2% vs. 31.2%, p = 0.003). Dental caries is also associated with oral health behaviors such as toothbrushing (twice or more times per day, 31.2% vs 42.2%, p = 0.003), dental flossing (34.5% vs 42.3%, p = 0.036) and frequent dental appointments (34.5% vs 41.2%, p = 0.04). Conclusions: We found a moderate prevalence of dental caries and in early age children there is a high percentage with multiple dental caries. Dental caries is associated with socio-demographic and behavioral aspects.